An Integrated Strategic Policy-Based Approach to Circular Economy, Corporate Risk Management, and Innovation Capability for Enhancing Sustainable Firm Performance at PT PLN (Persero) - Willy Novananda Siregar; Willy Arafah (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2026)
The development of electric vehicles (EV) in Indonesia presents economic opportunities as well as environmental challenges, particularly regarding the management of used electric vehicle battery waste. In this context, the implementation of circular economy becomes an important strategy for creating sustainable value through waste reduction, material recovery, and battery life cycle extension. However, the success of this approach is also influenced by the effectiveness of corporate risk management in anticipating regulatory, technological, and environmental risks arising from energy transformation. On the other hand, innovation capability is needed to drive efficiency and develop new business models capable of improving the competitiveness and profitability of companies. This study aims to integrate these three concepts with strategic policy as a mediating variable that ensures strategic alignment in achieving corporate performance objectives. The method used is an integrative literature review that examines literature from various disciplines to develop a conceptual model regarding the relationship between circular economy, corporate risk management, innovation capability, strategic policy, and sustainable firm performance. The results of the review indicate that circular economy, corporate risk management, and innovation capability have strong potential in driving improvements in firm performance, but their maximum contribution can only be realized through the support of adaptive and visionary strategic policies, particularly in large-scale organizations such as the state-owned enterprise PT PLN (Persero). Thus, this study provides a theoretical contribution in the development of a new conceptual framework as well as a strategic approach for strengthening the electric vehicle ecosystem and circular economy in Indonesia.